Engineering of Global Transcriptional Regulators (GTRs) in Aspergillus for Natural Product Discovery - Yujie Zhao; Qing Gong; Huawei Zhang (Journal of Fungi)
The Aspergillus genus is an important group of filamentous fungi, and the various biological activities of its secondary metabolites (SMs) have great biosynthetic potential. Despite over 4200 SMs having been isolated from Aspergillus spp., their metabolic potential remains unexplored due to the presence of numerous silent biosynthetic gene clusters (BGCs) in their genomes. Fortunately, over the last two decades, the global transcriptional regulator (GTR) engineering strategy has emerged as a powerful tool for activating these cryptic BGCs in order to synthesize previously undiscovered SMs from Aspergillus spp. This review highlights recent advances in fungal GTR engineering techniques, the regulatory mechanisms of GTRs, and current challenges and future perspectives for their application in natural product discovery in the genus Aspergillus.